Evolutionary changes in antimicrobial resistance of invasive Neisseria meningitidis isolates in Belgium from 2000 to 2010: increasing prevalence of penicillin nonsusceptibility. - Sophie Bertrand; Carion, Françoise; Wintjens, René; Vanessa Mathys; Vanhoof, Raymond (Antimicrob Agents Chemother, 2012)
This study was conducted to evaluate the evolution of the antimicrobial susceptibility of Neisseria meningitidis causing invasive diseases in Belgium in the period of January 2000 to December 2010. A total of 1,933 cases of N. meningitidis from invasive infections were analyzed by antimicrobial susceptibility testing at the Belgian Meningococcal Reference Centre. The majority of strains were susceptible to antibiotics that are currently used for the treatment and prophylaxis of meningococcal disease, but the prevalence of clinical isolates with reduced susceptibility to penicillin increased over the years. The phenotyping, genotyping, and determination of MICs of penicillin G were performed. The systematic shift of the curves toward higher penicillin MICs in the susceptible population indicated that this population became less sensitive to penicillin in this period. A 402-bp DNA fragment in the 3' end of penA was sequenced for the 296 nonsusceptible meningococcal strains isolated between 2000 and 2010 to examine the genetic diversity and evolution of their penA gene. In conclusion, the data obtained in our study support the statement that the position of penicillin G as a first choice in the treatment of invasive meningococcal diseases in Belgium should be reexamined. Despite an important number of isolates displaying a reduced susceptibility to penicillin, at present the expanded-spectrum cephalosporins, such as ceftriaxone, are not affected. The follow-up of the evolutionary changes in antimicrobial resistance has also proved to be essential for the recommendation of an appropriate antimicrobial treatment for invasive meningococcal diseases.
Keywords: 3' Flanking Region; alleles; Anti-Bacterial Agents; Bacterial Typing Techniques; Belgium; Biological Evolution; Ceftriaxone; Drug Resistance, Bacterial; Gene Frequency; Genes, Bacterial; Humans; Longitudinal Studies; Meningococcal Infections; Microbial Sensitivity Tests; Neisseria meningitidis; Penicillin G; Penicillin-Binding Proteins; Sequence Analysis, DNA